Ketimpangan Pembangunan Antar Wilayah di Pulau Sumatera, Pendekatan Spasial Ekonomi - Hidayat, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2023)
This study aims to examine development inequality between district/municipality and provincial regions to provide a more up-to-date assessment of the development inequality in Sumatera. Then, to explore the process of development inequality at a regional scale to better understand the spatial dynamics of development inequality. The dataset is secondary data from 2010-2020 from several BPS survey results. The analytical tool used to measure inequality is the Theil Index with a two-stage decomposition. Based on the results of the Theil Index, evidence was found of development inequality with a downward trend.